Development of a Digital Escape Room-Assisted E-Book in Environmental Science Courses - Nasution, Nanda Eska Anugrah (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
The use of advanced instructional technologies is essential for improving students' critical thinking skills and conceptual understanding, especially in environmental science. Digital escape room games, combined with e-books, offer an engaging and interactive learning experience that can significantly improve student outcomes in higher education settings. This study aimed to evaluate the validity and practicality of a digital escape room-assisted e-book for improving these skills among UIN KHAS Jember students. Using the ADDIE development model (Branch, 2009), the research assessed content validity and practicality through expert validation and trials. Content experts rated the e-book at 93.6% (very valid), while design experts rated it at 94.7% (very valid) for instructional media quality. In the individual trial, the e-book received a 91.9% score (very appealing), followed by a 94.1% score in the small group trial, and a 95.8% score in the field trial, both also categorized as very appealing. These results indicate that the digital escape room-assisted e-book is both highly valid and practical for use in environmental science course.